Evaluasi Desain Antarmuka Aplikasi Mobile BPJS Ketenagakerjaan Menggunakan Heuristic Evaluation - Fahry Nur Muhammad; Suprapto Suprapto; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
BPJSTK Mobile is a highly rated application owned by BPJS Ketenagakerjaan which has 4.0 score on Google Play, but also has some comments in the form of complaints and user frustration about missing features. Missing features can cause user satisfaction to decrease. User satisfaction is one of the determinants of usability level. This research was conducted using Heuristic evaluation method to find usability problem in user interface design. There are nine heuristic principles used, namely: visibility of system status, offer real world objects, user control and freedom, consistency and standard, error prevention, recognition rather than recall, flexibility and efficiency of use, aesthetic and minimalist design, and help user recognize, diagnose, and recover from errors. Data collection techniques used in the form of observation documents with assessment sheets, interviews, and observations using three evaluators. The evaluation is done by establishing the heuristic principles used, preparing the research instrument, selecting the evaluator, and collecting the data. Evaluation yielded problem finding with four categories of problem level: minor, medium, major, and catastrophic scattered in nine heuristic principles. Each of the findings of the problem was analyzed and given an improvement recommendation with a total of 22 recommendations with reference to relevant scientific or journaling articles